Efeito da combinação de antibióticos e sinvastatina sobre microrganismos de interesse endodôntico e na expressão de marcadores odontoblásticos - Machado, Juliana de Carvalho [UNESP] (2016)
Biological therapies have searching for substances/protocols, which promote microbial elimination and induce or stimulate pulp regeneration and completion of apical root development in young permanent teeth with pulp pathological processes . The objectives of this study were to evaluate the antimicrobial /anti-biofilm activity of some antibiotics combinations on endodontic microorganisms and the effect of the combination of antibiotics with the best antimicrobial action associated with simvastatin on expression of odontoblast markers by human dental pulp cells (HDPC). The antimicrobial activity of the following antibiotics : Metronidazole (ME), Ciprofloxacin (CI), Minocycline (MI), Doxycycline (DO) and Fosfomycin (FO), either alone or in double (ME+CI, ME+MI, ME+DO, ME+FO, CI+MI, CI+DO, CI+FO, DO+FO, MI+FO) or triple combinations (ME+CI+MI, ME+CI+FO, ME+MI+FO, ME+CI+DO, ME+DO+FO, CI+DO+FO, CI+MI+FO) were tested against Streptococcus mutans, Enterococcus faecalis, Actinomyces israelii and Candida albicans in planktonic conditions. Mono-species biofilm of E. faecalis and dual-species biofilms of E. faecalis and C. albicans were prepared in dentin blocks to test the anti -biofilm activity of antibiotic combinations with the best microbiological results. Antibiofilm effect of antibiotic combination on E. faecalis biofilm inside dentin tubules was also evaluated by confocal microscopy. Cultures of HDPC were exposed to the antibiotic combination with the best antimicrobial effect and simvastatin and determined cell viability, alkaline phosphatase activity, deposition of mineralization nodules and expression of Dspp (dentin sialophosphoprotein), important odontoblast markers of dentin mineralization. Data were analyzed statistically, considering p<0.05. All antibiotic combinations reduced statistically the growth of bacteria tested, except by CI+DO and DO+FO for A. israelii. ME+CI+MI and ME+MI+FO inhibited significantly growth of A. 11 israelii and E. faecalis, and ME+MI+FO eliminated S. mutans. ME+MI+FO and ME+CI+FO had the best effect against E. faecalis biofilm, in mono and dual -species biofilms and inside dentin tubules, similar to CHX. CI and ME+CI+FO affected HDPC viability, 1 and 7 days. ALP activity increased with the presence of simvastatin for all groups, except by CI and ME+CI+FO. Groups containing simvastatin had higher mineralized nodule deposition and higher DSPP expression than groups without simvastatin. It can be concluded that triple antibiotic combination of ME+CI+FO ha d remarkable effect against endodontic microorganisms, in planktonic and biofilm conditions. Simvastatin stimulated the expression of odontoblast markers of dentin mineralization by HDPC; however, its effect was reduced i n the presence of CI.